1998
DOI: 10.1111/j.1574-6968.1998.tb12795.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an endo-1,4-β-mannanase fromBacillus subtilisKU-1

Abstract: Endo‐1,4‐β‐mannanase was purified to homogeneity from the culture supernatant of Bacillus subtilis KU‐1 by ammonium sulfate precipitation, DEAE‐Toyopearl, phenyl‐Sepharose and FPLC Mono Q column chromatography by 810‐fold with 39% yield. The molecular mass of the enzyme was estimated to be 39 kDa by SDS‐PAGE and 40 kDa by gel filtration. It had a pI of 4.5 with maximum activity at pH 7.0 and 50–55°C. It was stable for 48 h between pH 4.5 and 9.0, and for 1 h up to 60°C. The enzyme activity was strongly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The pH 6.0 was the best pH for mannanase production from Bacillus circulans NT 6.7. The result was similar to mannanase production from Sclerotium rolfsii, pH 6.0 (Gübitz et al, 1996), but lower than that reported for mannanase production from Aspergillus niger, pH 7.0 (Ademark et al, 1998) and Bacillus subtilis KU-1, pH 7.0 (Zakaria et al, 1998). This study used locus bean gum because it's a common substrate used in mannanase industrial production.…”
Section: Effect Of Temperature and Ph On Mannanase Productionsupporting
confidence: 79%
“…The pH 6.0 was the best pH for mannanase production from Bacillus circulans NT 6.7. The result was similar to mannanase production from Sclerotium rolfsii, pH 6.0 (Gübitz et al, 1996), but lower than that reported for mannanase production from Aspergillus niger, pH 7.0 (Ademark et al, 1998) and Bacillus subtilis KU-1, pH 7.0 (Zakaria et al, 1998). This study used locus bean gum because it's a common substrate used in mannanase industrial production.…”
Section: Effect Of Temperature and Ph On Mannanase Productionsupporting
confidence: 79%
“…N16-5 sourced β-mannanase [26] showed the optimal temperature and pH at 70°C and 10.0 respectively, which was a basic functioning enzyme. A B. subtilis KU-1 sourced β-mannanase functions in the range of 50 to 55°C, and optimally catalyzes in pH 7.0 [27]. A β-mannanase from B. subtilis NM-39 was optimal at 50°C and pH 5.5 [28], which showed the most similar property as our β-mannanase at this point.…”
Section: Discussionmentioning
confidence: 50%
“…A β-mannanase from B. subtilis NM-39 was optimal at 50°C and pH 5.5 [28], which showed the most similar property as our β-mannanase at this point. Our β-mannanase expressed in P. pastoris X-33 optimally functions at 50ºC, which is the closest temperature to the body temperature compared to other reported β-mannanases [25][26][27][28]. Its optimal pH 6.0 is also in the pH range of gastric intestinal tract.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the 3D structure and H1A-23A mutation, the thermal stability of mannanase BCman from Bacillus subtilis was affected by its disulfide bond and metal-bonding site (His1-Glu336-His23); however, the mechanisms were not determined in details [31]. The specific activity of the purified MAN5A was 4,839 U/mg, which was higher than that of MANB48 (481.55 U/mg) [19] and of the β-mannanase from B. subtilis KU-1 (407.7 U/mg) [32], and only lower than that of β-mannanase purified from B. subtilis WY34 (8302.4 U/mg) [33]. MAN5A contains the acidic residues Glu-110 and Asp-149, in contrast to Gly and Asn, respectively, in MANB48.…”
Section: Discussionmentioning
confidence: 99%